A Bargaining Model of Friendly and Hostile Takeovers. (5th January 2016) - Loyola, Gino; Portilla, Yolanda
Abstract : A bargaining model is developed that characterizes the conditions under which a takeover will either be friendly, hostile, or unsuccessful when the target management can tilt the selling procedure toward a white knight. The conditions considered mainly involve private control benefits, toehold size, and breakup fees. Also established by the model are the conditions for an efficient takeover. The proposed framework of strong management influence on takeover outcome, an alternative modeling of hostility and the adoption of a negotiation procedure, rather than an auction setup with strong shareholder influence as in most of the existing literature, delivers new insights into the US market of corporate control, which are consistent with the available evidence.